Ceramiche fini, Ceramica Africana da Cucina e lucerne dai contesti medio imperiali delle 'Terme di Elagabalo' a Roma: ruoli, produzioni ed origini - Radaelli, Edoardo (Rei Cretariae Romanae Fautorum Acta, 2022)
The analysis of all fine wares, African cooking ware, and lamps from the Middle Imperial contexts (2nd– early 3rd centuries AD) found during the excavations carried out in the building known as the ‘Terme di Elagabalo’ in Rome allowed to distinguish between in-phase, intrusive and residual vessels so as to understand the formation processes of the contexts considered. In-phase finds – also determining the differences in the quantities between locally produced and imported forms – offer significant data about the ceramic supply of the Capital, especially for the early 3rd century AD which is rather under-represented in the available ceramic publications about Rome.